2010
DOI: 10.1111/j.1369-1600.2010.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Noribogaine, but not 18‐MC, exhibits similar actions as ibogaine on GDNF expression and ethanol self‐administration

Abstract: Ibogaine is a naturally occurring alkaloid that has been reported to decrease various adverse phenotypes associated with exposure to drugs of abuse and alcohol in human and rodent models. Unfortunately, ibogaine cannot be used as a medication to treat addiction because of severe side effects. Previously, we reported that the desirable actions of ibogaine to reduce self-administration of, and relapse to, alcohol consumption are mediated via the upregulation of the expression of the glial cell line-derived neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Finally, systemic injection of the α3β4* nAChR-selective antagonist 18-methoxycoranaridine (18-MC) reduces ethanol consumption in alcohol-preferring rats (Rezvani et al, 1997). However, direct infusion of 18-MC into the VTA fails to reduce alcohol consumption (Carnicella et al, 2010) in rats consistent with data indicating low expression of β4* nAChRs in VTA DAergic neurons (Gotti et al, 2010; Zhao-Shea et al, 2011). …”
Section: Neuronal Nachrs and Alcohol: Identifying Relevant Subtypes: supporting
confidence: 61%
“…Finally, systemic injection of the α3β4* nAChR-selective antagonist 18-methoxycoranaridine (18-MC) reduces ethanol consumption in alcohol-preferring rats (Rezvani et al, 1997). However, direct infusion of 18-MC into the VTA fails to reduce alcohol consumption (Carnicella et al, 2010) in rats consistent with data indicating low expression of β4* nAChRs in VTA DAergic neurons (Gotti et al, 2010; Zhao-Shea et al, 2011). …”
Section: Neuronal Nachrs and Alcohol: Identifying Relevant Subtypes: supporting
confidence: 61%
“…Animal behavioral results show that (−)-noribogaine possess a similar anti-addictive profile as that for (−)-ibogaine (Glick et al, 1996). Interestingly, the infusion of (−)-noribogaine directly into the ventral tegmental area results in a significant and long-lasting decrease in ethanol self-administration by rats that is not observed by (±)-18-MC (Carnicella et al, 2010). Based on these results, the authors suggested that (−)-noribogaine and (±)-18-MC have different mechanisms and sites of action.…”
Section: Discussionmentioning
confidence: 88%
“…These well-documented anti-alcohol properties of varenicline seem to be dependent on the activation of α4 nAChRs (Hendrickson et al, 2010). In contrast, α7 (Kuzmin et al, 2009) and α3β4 nAChRs (Carnicella et al, 2010; Cippitelli et al, 2015b) may not be involved in alcohol reinforcement. Consistent with this literature, we have recently demonstrated the efficacy of varenicline in decreasing alcohol self-administration at doses that also decreased nicotine self-administraton in an operant co-administration paradigm (Cippitelli et al, 2015c).…”
Section: Introductionmentioning
confidence: 93%